Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Write the nth term of the following sequence in terms of the first term of the sequence.

2, -4, 8, -16, . . .


Sagot :

Answer:

        [tex]\bold{a_n=2\cdot(-2)^{n-1}}\\\\or\\\\\bold{a_n=(-1)^{n-1}\cdot2^{n}}[/tex]

Step-by-step explanation:

-4÷2 = -2

8÷(-4) = -2

-16÷8 = -2

So this is a geometric sequence with the first term of 2 and a common ratio of -2

the nth term of a geometric sequence:  [tex]a_n=a_1\cdot r^{n-1}[/tex]

Therefore:

            [tex]a_n=2\cdot(-2)^{n-1}\\\\a_n=2\cdot(-1\cdot2)^{n-1}=2\cdot(-1)^{n-1}\cdot2^{n-1}=(-1)^{n-1}\cdot2^{n-1+1}\\\\a_n=(-1)^{n-1}\cdot2^{n}[/tex]